PENGARUH ROA, CR, TATO, DER, DAN ROE TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Fachrurrozi, Muhammad Faizal Putra; Ma’sumah, Siti; Rossana, Laila (Jurnal Riset Keuangan dan Akuntansi, 2024)
This study which aims to determine the analyzing of the partial and simultaneous influence of the Return On Asset (ROA), Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Return On Equity (ROE) variables on stock returns in transportation and logistics sector companies listed on the BEI for the 2019-2022 period. This study uses quantitative methods with secondary data collection techniques collected by data documentation methods. Based on the results of the analysis and discussion that can be taken from this research is that partially the variables ROA, CR, TATO, DER and ROE have no significant effect on stock returns in transportation and logistics sector companies listed on the BEI for the 2019-2022 period. Simultaneously ROA, CR, TATO, DER and ROE have no significant effect on stock returns in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Keywords: ROA, CR, TATO, DER, ROE and Stock Return